Urine Proteomics Revealed a Significant Correlation Between Urine-Fibronectin Abundance and Estimated-GFR Decline in Patients with Bardet-Biedl Syndrome - Marianna Caterino; Miriam Zacchia; Michele Costanzo; Giuliana Bruno; Davide Arcaniolo; Francesco Trepiccione; Rosa Anna Siciliano; Maria Fiorella Mazzeo; Margherita Ruoppolo; Giovambattista Capasso (Karger Publishers, 2018)
Background:/Aims: Renal disease is a common cause of morbidity in patients with Bardet-Biedl syndrome (BBS), however the severity of kidney dysfunction is highly variable. To date, there is little information on the pathogenesis, the risk and predictor factors for poor renal outcome in this setting. The present study aims to analyze the spectrum of urinary proteins in BBS patients, in order to potentially identify 1) disease-specific proteomic profiles that may differentiate the patients from normal subjects; 2) urinary markers of renal dysfunction. Methods: Fourteen individuals (7 males and 7 females) with a clinical diagnosis of BBS have been selected in this study. A pool of 10 aged-matched males and 10 aged-matched females have been used as controls for proteomic analysis. The glomerular filtration rate (eGFR) has been estimated using the CKD-EPI formula. Variability of eGFR has been retrospectively assessed calculating average annual eGFR decline (ΔeGFR) in a mean follow-up period of 4 years (3-7). Results: 42 proteins were significantly over- or under-represented in BBS patients compared with controls; the majority of these proteins are involved in fibrosis, cell adhesion and extracellular matrix organization. Statistic studies revealed a significant correlation between urine fibronectin (u-FN) (r2=0.28; p<0.05), CD44 antigen (r2 =0.35; p<0.03) and lysosomal alfa glucosidase ( r20.27; p<0.05) abundance with the eGFR. In addition, u-FN (r2 =0.2389; p<0.05) was significantly correlated with ΔeGFR. Conclusion: The present study demonstrates that urine proteome of BBS patients differs from that of normal subjects; in addition, kidney dysfunction correlated with urine abundance of known markers of renal fibrosis.